When the Danube ran red - Ozsváth, Zsuzsanna 1934- (Religion, theology, and the Holocaust, 2010)
Hanna -- Relocations -- Past and present -- A dream disrupted -- Changes -- Erzsi -- Options -- Pali -- Before the storm -- Disaster strikes : March 19 -- Plans for the future -- Measures taken -- The new world -- Ghettoization -- The ghetto house -- The children of 10 Abonyi Street -- A miracle -- The return of horror -- Evil tidings -- Together -- Homeless -- The Vatican house -- Witches' Shabbat -- Alone -- The siege -- Walking across the underworld -- The "White Cross Hospital" -- Going home -- Epilogue